2013
DOI: 10.1186/1471-2490-13-38
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial to assess the efficacy and cost-effectiveness of urinary catheters with silver alloy coating in spinal cord injured patients: trial protocol

Abstract: BackgroundPatients with non-acute spinal cord injury that carry indwelling urinary catheters have an increased risk of urinary tract infection (UTIs). Antiseptic Silver Alloy-Coated Silicone Urinary Catheters seems to be a promising intervention to reduce UTIs; however, actual evidence cannot be extrapolated to spinal cord injured patients. The aim of this trial is to make a comparison between the use of antiseptic silver alloy-coated silicone urinary catheters and the use of standard urinary catheters in spin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…For example, a multicenter randomized controlled trial involving participants requiring short-term (≤14 days) catheterization compared commercially available Ag alloy-coated latex catheters (>2000 patients) with standard PTFE-coated latex catheters (>2000 patients) and concluded that the Ag alloy-coated catheters were not effective in reducing the incidence of symptomatic CAUTIs . On the other hand, two smaller studies showed 35% and 47% reductions in the CAUTIs with Ag alloy and Ag-alloy hydrogel catheters, respectively, compared to the standard catheter. , The reasons for the differences in findings are likely to be multifactorial involving how the clinical trials were carried out and the nature of the Ag-coated catheters such as Ag release rate and surface properties.…”
Section: Dual-functional Coatings For Biomedical Applicationsmentioning
confidence: 99%
“…For example, a multicenter randomized controlled trial involving participants requiring short-term (≤14 days) catheterization compared commercially available Ag alloy-coated latex catheters (>2000 patients) with standard PTFE-coated latex catheters (>2000 patients) and concluded that the Ag alloy-coated catheters were not effective in reducing the incidence of symptomatic CAUTIs . On the other hand, two smaller studies showed 35% and 47% reductions in the CAUTIs with Ag alloy and Ag-alloy hydrogel catheters, respectively, compared to the standard catheter. , The reasons for the differences in findings are likely to be multifactorial involving how the clinical trials were carried out and the nature of the Ag-coated catheters such as Ag release rate and surface properties.…”
Section: Dual-functional Coatings For Biomedical Applicationsmentioning
confidence: 99%
“…[75] Silver and its formulations were studied in different polymeric surfaces, including silicone, polyurethane, and latex, and tested against a broad spectrum of Gram-positive and Gramnegative bacteria, in both in vitro and in vivo studies. [67,68,74,[76][77][78][79] For all these reasons, silver is a promising coating for ureteral stent devices, and it has been widely investigated for coating application in the urinary tract context. Nonetheless, contradicting studies already described the ineffectiveness of this strategy, reporting no significant advantages against UTIs.…”
Section: Coatingsmentioning
confidence: 99%
“…Antibiotic therapies may affect not only the target microorganisms but also the hostassociated microbial communities, particularly those in the intestine [29]. In MS and SCI patients, neurogenic lower urinary tract dysfunction, respiratory and skin problems frequently occur [30] and hence this population is at risk of developing infections that often require antibiotic treatment [31,32]. Therefore, they might also be at risk of altered gut microbiota composition.…”
Section: Introductionmentioning
confidence: 99%